Committee on Transport Policy and Coordination Papers 141-187 - Planning Commission (Planning Commission, 1961)
The article is divided into two parts In the first part, the author has dealt with the pros and cons of centralisation, and in the second mart, the question of developing Line management has been discussed. The Gam object of this article is to discuss the problem of railway organisation by setting out some basic questions to be answered Some lessons of the past have also been reviewed, from the pre-nationalisation railway companies to Railway Executive, the B.T.G. and the area boards. Lastly, an attempt has been made to answer the questions by suggesting some ways in which the White Paper’s outline of the future railway organisation Could be developed.
Transport Division
Transport Division